Isolation and Identification of Acetic Acid Producer from Mixed Culture of Soil and Banana Stem Waste in Anaerobic Condition - Mohd Faizan, Jamaluddin; N., Zainol (World Academy of Reseacrh and Publication, 2012)
Anaerobic fermentation is a feasible option and a low-cost process for production of acetic acid. However, if the material used for production is hardly degradable such as lignocelluloses waste, the process does need the bacteria that are versatile in order to produce a high amount of yield and degrade combination of substrate. Banana stem waste is lignocellulosic waste, and it contained high amount of cellulose that can be used as a substrate for acetic acid production. Meanwhile, mixed culture from soil did contain high amount and variety species of bacteria. In order to increase the yield and find the suitable bacteria for the process, the pure strain needs to be obtained. Therefore, isolation and identification of bacteria need to be done. Isolation and identification of acetic acid producer from mixed culture of soil and banana stem waste was done. Isolation was done by aseptically serial diluted. Culture from each dilution will be cultured anaerobically towards selective medium that consists of glucose. 15 strains from 57 strains isolated able to utilize glucose to produce acetic acid. From 15 strains, one strain able to produce acetic acid up to 1.8 g/l and can degrade lignin. This strain was chosen to be identified using gram stain, biochemical test using BIOLOG kit. From the identification results, the strain was known as Enterobacter Soli. This strain can degrade a variety of substrate, including lignin, cellulose and almost all types of re- ducing sugar (C5-C6) and produce a high amount of acetic acid by using complex raw material as lignocellulosic waste.